Inter-year consistencies and discrepancies on intestinal microbiota for overwintering relict gulls: correlations with food composition and implications for environmental adaptation - Wu, Hong; Yao, Hongyu; Sun, Menglin; Wang, Ran; Zhang, Zeming; Wu, Nan; Zhao, Dapeng (Frontiers in Microbiology, 2024)
The gut microbiota of migratory birds is influenced by their food choices, and exploring the potential relationship between diet composition and gut microbiota can help better protect related species. By integrating non-invasive sampling techniques, high-throughput sequencing technology, and microscopic examination technology, this study presents the first evidence on diet composition during overwintering periods as well as the potential relationship between diet composition and gut microbiota in wild relict gulls (Larus relictus). Thirty-five fecal samples from two consecutive overwintering periods (2021 and 2022 overwintering periods) in Tianjin coastal wetland were used to investigate inter-year consistencies and discrepancies on diet composition and gut microbiota in wild Larus relictus. It was found that the common dominant phyla of both 2021 and 2022 group included Firmicutes, Proteobacteria, Chloroflexi and Actinobacteriota. The common dominant genera were Catellicoccus and Ilumatobacter. The diversity of gut microbiome in 2022 group was higher, while the richness was not significantly different. Based on the high-throughput sequencing technology of 18S rDNA, the study found that the dominant classes within the diet components of Larus relictus included Polychaeta, Bivalvia, Malacostraca, Gastropoda, unclassified_p__Dinoflagellata, Dinophyceae, and Ostracoda. Among them, Bivalvia, Malacostraca, and Gastropoda were also found with microscopic examination technology from the same samples. The abundance of Fusobacteriota and Cetobacterium were positively correlated with the abundance of Bivalvia and Malacostraca; while the abundance of Psychrobacter and Breznakia were negatively correlated with the abundance of Malacostraca and Gastropoda. Findings from this study could provide scientific references for health monitoring and conservation of relict gulls.